PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR INKLUSIF KOTA YOGYAKARTA - Abdul Rahim; Taryatman Taryatman (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: This study is based on the problem of children with special needs who have not been able to participate fully in physical education education in Inclusive Elementary School in Yogyakarta City. This is because the gatekeepers have not understood the poultry learning program for children with special needs in the Inclusive Elementary School. Through this research, an adaptive adaptive learning resource book for children with disabilities in Inclusive Elementary School will be developed. It is expected that this instructional book can facilitate teachers in designing learning pemas for children with special needs in Elementary School. The results of research progress reports found data, namely: implementation of learning pemas in 8 elementary schools of education inclusive is not optimal. In learning pemas need to do: 1) planning, 2) process and 3) evaluation of learning tailored to the needs of students with special needs.